Effects of GA4+7+BA and CPPU on russeting and fruit quality in apple (Malus Ã— domestica) - Sharma, Sajan; Sharma, N; Sharma, D P; Chauhan, Neena (The Indian Journal of Agricultural Sciences, 2020)
Apple (Malus × domestica Borkh.) production is now being affected by the changing climate which has led to reduction in quality thereby, these fruits command low returns in the market. As it is the most important temperate fruit crop of Himachal Pradesh, it still requires a great improvisation in quality. The present study was conducted in 2017-18 with various plant growth regulator practices on eight year old apple trees cv. ‘Scarlet Spur II’. Application of GA4+7+BA at 2.5 and 5 ppm when given at petal fall and two times later at 10 days interval recorded minimum russet formation (Score:1.17), increased fruit length (68.93 mm) as well as increased L/D ratio (1.07), TSS and sugar content in apple. However, CPPU at 10 ppm when applied at petal fall stage recorded higher fruit diameter (70.89 mm), fruit weight (155.56 g), fruit volume (102.94 cc), TSS (10.72 ºBrix), total sugars (9.11%) and reducing sugars (4.87%).